Does Project Noise Interfere With Guest Comfort? A Case Study at Radisson Blu Uluwatu Hotel - Silvana Mewengkang; Asterlita R. Wenas; Silvana Sumoked; Margresya Rompas; Deisy Ch. Andih; Fonny Sangari; Pangemanan, Jemmy (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
Radisson Bali Uluwatu is one of the 5-star hotels in Bali. Since mid-2023, the hotel has experienced many complaints from guests staying due to the construction project of the hotel and villa construction, which is located east and west of the hotel. This study aims to determine the noise disturbance of construction projects on guest comfort at Radisson Blu Bali Uluwatu Hotel. This research uses data collection methods by means of observation, interviews, and documentation. The data obtained was then analyzed and presented qualitatively. The results showed how to understand and apply soundproofing methods to reduce noise entering the hotel room. The conclusion that can be drawn is that the application of acoustic systems in guest rooms is able to provide comfort while in the room, so that guests feel safe, comfortable, and satisfied with the hotel atmosphere, and will have a positive impact on the Radisson Blu Bali Uluwatu Hotel